2012
DOI: 10.1523/jneurosci.5828-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Receptor 30 Mediates Rapid Neuroprotective Effects of Estrogen via Depression of NR2B-Containing NMDA Receptors

Abstract: 17-␤-Estradiol (E2)is a steroid hormone involved in neuroprotection against excitotoxicity and other forms of brain injury. Through genomic and nongenomic mechanisms, E2 modulates neuronal excitability and signal transmission by regulating NMDA and non-NMDA receptors. However, the mechanisms and identity of the receptors involved remain unclear, even though studies have suggested that estrogen G-protein-coupled receptor 30 (GPR30) is linked to protection against ischemic injury. In the culture cortical neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 70 publications
2
89
0
Order By: Relevance
“…In the present study, a mouse model of transient focal cerebral ischemia induced by a 2 h MCAO and 24 h reperfusion was used to evaluate the neuroprotective effects of sesamin. Previous studies have reported that MCAO damages the structure of the neurons and other cells that support the neurons [20,34] and decreases neurological function [20]. Our results suggested that sesamin reduces the infract volume in the brain of MCAO mice and improves the neurological deficit score.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, a mouse model of transient focal cerebral ischemia induced by a 2 h MCAO and 24 h reperfusion was used to evaluate the neuroprotective effects of sesamin. Previous studies have reported that MCAO damages the structure of the neurons and other cells that support the neurons [20,34] and decreases neurological function [20]. Our results suggested that sesamin reduces the infract volume in the brain of MCAO mice and improves the neurological deficit score.…”
Section: Discussionsupporting
confidence: 58%
“…The Animal Care and Use Committee of the Fourth Military Medical University approved all of the animal protocols used. Prefrontal cortex neurons were cultured as described previously [20]. Briefly, the prefrontal cortex was dissected, minced, and trypsinized at 37ºC for 10 min using 0.25% trypsin (Invitrogen, Carlsbad, CA).…”
Section: Primary Mouse Cortical Neuronal Culturementioning
confidence: 99%
“…Although some earlier studies observed immunoreactivity corresponding to the classical, nuclear GR in the plasma membrane (12,15,40,42), more recent ones have proposed that the fast actions of CORT in hippocampal neurons are mediated by translocated nuclear MR (7,43). It is pertinent to note that recent work has implicated an orphan GPCR in fast signaling by two other steroid hormones, estradiol and aldosterone (44,45); the latter is enzymatically (18-hydroxylase and 18-hydroxysteroid dehydrogenase) derived from CORT.…”
Section: Discussionmentioning
confidence: 97%
“…Cultured prefrontal cortex neurons were prepared as described previously [26]. Briefly, the prefrontal cortex was dissected, minced, and trypsinized for 15 min using 0.125 % trypsin (Invitrogen, Carlsbad, CA).…”
Section: Primary Cortical Neuronal Culture and Aβ 1-42 Treatmentmentioning
confidence: 99%
“…Western blot analysis was performed as described previously [26]. Equal amounts of protein (50 μg/lane) from the cultures were separated and electrotransferred onto polyvinylidene fluoride membranes (Invitrogen), which were incubated with rabbit polyclonal anti-tau (1:1000; Santa Cruz Biotechnology, Santa Cruz, CA), rabbit polyclonal anti-p-Tau (Ser235) (1:1000; Santa Cruz Biotechnology), rabbit polyclonal antip-Tau (Thr205) (1:1000; Santa Cruz Biotechnology), and mouse monoclonal anti-β-actin (1:4000; Sigma) as an internal control.…”
Section: Western Blot Analysismentioning
confidence: 99%